2011
DOI: 10.1017/s1751731110001850
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an immunomodulatory feed additive on the development of mastitis in a mouse infection model using four bovine-origin isolates

Abstract: The goal of this study was to examine the ability of a commercially available feed additive (OmniGen-AF) to reduce mammary infections caused by a single strain of mastitic pathogens (Streptococcus uberis, Escherichia coli, Staphylococcus aureus and Klebsiella pneumoniae) and to examine the effects of the additive on markers of mammary immunity. Four experiments were completed using a murine model of bovine mastitis. Infection progression was examined using Sybr-green-and TaqMan-based quantitative PCR assays of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…We previously reported that one of the most widely used immunomodulatory feed supplements, YCA, decreased mammary infections in dairy cows and improved milk production, 4 and improved innate and adaptive immune responses function in immune-challenged ruminant livestock. [1][2][3][4][5][6] This study closes an important gap in our knowledge, as it helps to explain the improved innate and adaptive immune responses reported in ruminant livestock fed YCA. At the same time, we want to caution the reader, as gene expression may or may not translate into changes on the protein level and/or functional changes like our previously observed TCA-induced changes in L-selectin gene and protein expression across various ruminant species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that one of the most widely used immunomodulatory feed supplements, YCA, decreased mammary infections in dairy cows and improved milk production, 4 and improved innate and adaptive immune responses function in immune-challenged ruminant livestock. [1][2][3][4][5][6] This study closes an important gap in our knowledge, as it helps to explain the improved innate and adaptive immune responses reported in ruminant livestock fed YCA. At the same time, we want to caution the reader, as gene expression may or may not translate into changes on the protein level and/or functional changes like our previously observed TCA-induced changes in L-selectin gene and protein expression across various ruminant species.…”
Section: Discussionmentioning
confidence: 99%
“…We documented in several studies that feeding a yeast-containing additive (YCA; OmniGen-AF; Prince Agri Products, Inc., Quincy, IL, USA) at the recommended inclusion rate (0.25-0.50 wt% of diet) promotes immune function and maintains health and production in immune-or stress-challenged ruminant species and rodent models. [1][2][3][4][5][6] For example, Holstein heifers supplemented for 30 d with YCA had significantly increased surface-bound and internalized Escherichia coli in neutrophils. 5 Feeding YCA to the same animals tended to increase binding and uptake of Staphylococcus aureus by neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of an immunomodulatory product, OmniGen‐AF (Prince Agri Products Inc., NJ, USA) has been shown to stimulate the production of immune markers in experimental animals and ruminants, including dairy cattle . The current study was conducted to determine if immune marker stimulation observed in trials in North America in dairy heifers, rodents, sheep and in housed cows fed a total mixed ration could be repeated in pasture‐fed cows under Australian conditions.…”
mentioning
confidence: 99%
“…Similar parameters reported in previous studies (with both streptococcal and staphylococcal species) were also applied in this work, such as the number of bacteria used as inoculum (~10 2 CFU per gland)(Chandler 1970b; Demon et al 2013; Rowson et al 2011). Similar to what has been reported for S. aureus infections (Brouillette and Malouin 2005; Schmelcher et al 2012b), also in Streptococcus -induced mastitis, the level of infection is largely independent of the bacterial concentration of the inoculum, and maximal infection with bacterial numbers larger than 10 8 CFU per gland can be reached even with relatively low-concentrated inocula (Chandler 1970a).…”
Section: Discussionmentioning
confidence: 94%
“…Various previous studies have used the mouse model of bovine mastitis for investigating Streptococcus -induced mammary gland infections and the efficacy of different agents for preventing or treating them (Anderson and Craven 1984; Chandler 1970a; Demon et al 2013; Rowson et al 2011), even though the body of literature dealing with streptococcal infections is still relatively small compared to the multitude of publications available on mouse models of S. aureus -induced bovine mastitis (reviewed in Brouillette and Malouin 2005). Similar parameters reported in previous studies (with both streptococcal and staphylococcal species) were also applied in this work, such as the number of bacteria used as inoculum (~10 2 CFU per gland)(Chandler 1970b; Demon et al 2013; Rowson et al 2011).…”
Section: Discussionmentioning
confidence: 99%